Valoración de la terapia combinada de Enalapril con Irbesartán sobre la función renal en pacientes diabéticos tipo 2 - Rodríguez Hernández, Andrea (2007)
The present work pretends to add evidence that holds back the use of enalapril and irbersartan as a combination in a sample of diabetic patients of the ospitalMexicoinCosta Rica. Methods: A sample of diabetic patients that were attended in the nephrology service of this hospital during 2004-2006 was chosen.  They were checked on renal function and the possible correlation between the renal function and nephroprotective therapy, in this case ACEs alone or ACEs plus ARBs in combination. Results: The proportion of patients that used the treatment as a combination and improve their renal function was more elevated in the combination group. Conclusions: The data found indicates a possible advantage for the patients taking the combination of these drugs as means of nephroprotection, if we compared the control group (ACEs alone).